KAJIAN STRUKTUR ARANG-PIROLISIS, ARANG-HIDRO DAN KARBON AKTIF DARI KAYU Acacia mangium Willd. MENGGUNAKAN DIFRAKSI SINAR-X - Saptadi Darmawan; Wasrin Syafii; Nyoman J Wistara; Akhirudin Maddu; Gustan Pari (BRIN Publishing, 2015)
Activated carbon has been used widely for various applications. Hydro-char which is hydrothermally carbonized from biomass could be used as an alternative precursor for activated carbon manufacture, which is commonly obtained from pyrolized-char. This paper observes crystalline structure of Acacia mangium’s pyrolized-char and hydro-char using XRD (X-raydiffraction). The mangium wood was carbonized in 200°C and 300°C and depth analysis was conducted based on activated carbon product. Result shows carbon maturity index and aromaticity from both precursors (conventional and alternative) tends to increase after being activated; interlayer spacing (d002) is getting closer; meanwhile, crystallinity is greater; and the number, height as well as width of aromatic layers are increasing. Hydro-char exhibited crystallinity degree, maturity and aromaticity lower than those of the pyrolized-char obtained at 300°C carbonization, with the greater volatile content. Both types of char perform carbon structure with amorphous texture. The greatest iodine adsorption is achieved by hydro-char which was carbonized at 300°C. In general, XRD analysis on low temperature carbonization of pyrolized-char and hydro-char could predict the porosity of activated carbon.